Recognition of Recording and Reporting Accounting at Tour and Travel - Seto Sulaksono Adi Wibowo; Siti Ulin Nikmah (Pusat P2M Politeknik Negeri Batam, 2016)
This final assignment is done in tour and travel. The company didn’t record any transaction conducted, the company only used receipt as transaction evidence. So that the company experienced difficulties in determining the exact profits obtained. Based these problems, the researcher gives a guide in recording transactions and making financial statements so company can keep records in every transactions to improve accounting process especially in making financial statements.